Machiavellian, Organizational Commitment, Retaliation, Self-Efficacy, Religiosity and Intention Whistleblowing - Luqman Hakim; Adhelia Natasya Fikri; Mitsalina Tantri (Program Studi S3 Ilmu Manajemen, 2022)
This study aims to determine the effect, (1) nature machiavellian on intention whistleblowing, (2) organizational commitment to intention whistleblowing, (3) retaliation to intention whistleblowing, (4) self-efficacy on intention whistleblowing, (5) religiosity towards intention whistleblowing. This research is a type of quantitative research. The data collection method used is primary data obtained by using a questionnaire. The population in this study are internal auditors who work in companies in the South Jakarta area and are registered with the Internal Audit Education Foundation (YPIA) and have worked for more than 1 year. The sampling technique used is purposive sampling with sampling quotas which produced 36 respondents. This test uses SPSS Version 25 as a data analysis tool. The results of this study indicate that (1) Nature machiavellian no effect on intention whistleblowing, (2) Organizational commitment affects intention whistleblowing, (3) Retaliation affects intention whistleblowing, (4) Self-efficacyno effect on intention whistleblowing, and (5) Religiosity has no effect on intention whistleblowing.